PENINGKATKAN KEMAMPUAN KONEKSI DAN PEMECAHAN MASALAH MATEMATIKA SISWA SMA MELALUI PEMBELAJARAN KOOPERATIF - Muhammad Kholidi; Sahat Saragih (Study Program of Mathematics Education of Unimed Postgraduate Program, 2010)
This study aims to (a) describe the mathematical connection capability (KKM), and math problem-solving ability (KPMM) students, (b) analyzing the cooperative learning approach (PPK) in setting student achievement team devisions (STAD) compared with conventional learning approach (PPKon ) in an effort to improve the KKM and KPMM (c) analyzing the ability of mathematics (KM) in the setting of high, medium and low in an effort to improve the KKM and KPMM (d) analyze the interaction factor learning approach (PPK, PPKon) with KM factor in influencing the increase KPMM or KKM. This study uses 2 x 2 factorial pretest-posttest control group design. The research population is high school students in the Tanjungbalai City. At random, one school was chosen as research subjects. Then randomly selected two classes of some parallel class XII IPA. Experimental class were treated Cooperative Learning Approach (PPK) and the control classes were given treatment Learning Approach Conventional (PPKon). KKM’s data obtained from 5 grains KKM test, KPMM’s data were obtained from 5 grains KPMM tests, and observation sheet. Data were analyzed descriptively with ANOVA two-lane with 2 x 2 factorial, with a gain-gain is normalized as a variant. Technical analysis using SPSS 16.0 for Windows PCs. Tests performed on the null hypothesis significance level of 5%. The main result of this study were (1) Significantly there is a difference between the PPK and PPKon of KKM and KPMM increase the value of F = 18 297 and P-value = 0.000 for KKM, and F = 19 309 and P-value = 0.000 for each KPMM with respective P-value < a = 0.05, (2) Significantly there is a difference between the PPK and KKM PPKon on the increase and the KPMM based on student ability (high, medium, and low) with a value of F = 9629 and P-value = 0.000 for KKM , and F = 10 946 and P-value = 0.000 for KPMM with each P-value < a= 0.05, (3) The results of analysis obtained 69.67% of students in the group of PPK, are able to apply the realm of KKM, whereas only 58 PPKon, 73%, from analysis of the PPK gained 77.22% of students who understand the problem (MM), 69.29% of students are able to plan completion (MP), 65.8% students are able to solve the problem (SM), and 51.8% students look back on the job (MK). While PPKon group, only 70.88% of students who understand the problem (MM), 57.26% of students are able to plan completion (MP), 50.74% students are able to solve the problem (SM), and 41.2% students look back work (MK). Based on the results of this study can be concluded that the PPK is the right approach, in an effort to improve connectivity and problem-solving ability mathematics students.